1989
DOI: 10.3109/00365518909091556
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glutamate–a prognostic marker of cancer and of other immunodeficiency syndromes?

Abstract: Elevated plasma levels of glutamate (GLU) have been reported to occur in patients with malignancies and other immunodeficiency syndromes (IDS). To evaluate, whether GLU is useful as prognostic indicator, the plasma concentrations were determined in patients with colorectal carcinoma (CRC), with breast cancer (BRC), and with HIV-infection (HIV). The results were correlated with the disease-stages, and compared with data obtained from patients with benign diseases of the same organ, as well as from sex-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
3
15
1
Order By: Relevance
“…Previous studies in humans have revealed that glutamic acid concentration increases in tumour tissue when compared to unaffected tissues, and these changes are strongly related to advancement of malignancy stage of the neoplastic process (19,22,23). Similar results were reported in studies on dogs with mammary gland tumours and skin tumours, where evaluation of amino acids in malignant tumour tissues and serum has shown increased glutamic acid concentration in both these compartments when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies in humans have revealed that glutamic acid concentration increases in tumour tissue when compared to unaffected tissues, and these changes are strongly related to advancement of malignancy stage of the neoplastic process (19,22,23). Similar results were reported in studies on dogs with mammary gland tumours and skin tumours, where evaluation of amino acids in malignant tumour tissues and serum has shown increased glutamic acid concentration in both these compartments when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, a significant number of clinical studies have consistently shown strong correlation between immunodeficiency, such as occurs in AIDS (16 -18) or in malignancies (19,20), and the deregulation of plasma glutamate levels. However, both the cells producing glutamate and the physiological mechanisms underlying glutamate actions in the immune response remain far from being elucidated.…”
mentioning
confidence: 99%
“…The glutamate concentration is higher in malignant and purulent effusions and lower in cardial and cirrhotic effusions. This may be due to incomplete deamidation of glutamine to glutamate as a result of hypoxia (8), and the secretion of glutamate by tumour cells (8,9). Glutamine can also be converted into glutamate by macrophages and fibroblasts (10).…”
Section: Discussionmentioning
confidence: 99%